The Influence of Leadership, Self Efficacy, and Career Development on Employee Performance: Pengaruh Leadership, Self Efficacy, dan Pengembangan Karir terhadap Prestasi Kerja Karyawan - Sari, Ainul Nurma; Sari, Dewi Komala (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this study was to determine the effect of Leadership, Self Efficacy, and Career Development on Employee Work Performance either partially or simultaneously. And to find out the most significant influence between the influence of Leadership, Self Efficacy, and Career Development on Employee Work Achievement at CV. Amanda Son. The research method in this study uses a quantitative approach with primary data sources. The data in this study used tabulated data from respondents from the questionnaire results. The sample used in this study was 54 employees at CV. Amanda Son. This primary data was obtained from a questionnaire whose measurement was using a Likert scale which was tested for validity and reliability. The analysis used is multiple linear regression analysis, coefficient of determination (R2), partial correlation coefficient, t test, F test and classical assumption test using SPSS program. This study proves that leadership has an effect on work performance. Self efficacy has an effect on work performance. Career development affects work performance. Leadership, self efficacy, and career development affect work performance.